Monetary policy and the stock market in South Africa: how do South African equity prices respond to expected and unexpected changes in the repo rate? - Ramatlo, Tshegofatso (School of Economics, 2020)
This analyses the impact of unexpected changes in monetary policy on the South African equity market over the period 2005 -2018. In an attempt to understand this relationship, two main views have emerged. The wealth effect suggests that monetary policy changes have an indirect effect on the stock market, via changes in the value of private portfolios. On the other hand, it has been argued that the stock market is an independent source of macroeconomic volatility to which policy makers may wish to consider. This paper applies an event study approach to examine the stock market reaction to monetary policy. Furthermore, to understand the economic sources underpinning that reaction a Vector autoregressive model is estimated. The results suggest that on average, a surprise rate hike of 100 basis points causes short term JSE All Share index total returns to decline by 2.71%. We also find that the stock market reacts positively (negatively) to expansionary (contractionary) unexpected monetary policy actions due to revised market expectations about future dividends, excess premiums and the discount rate. The findings are crucial for central bank policy makers and JSE stock market investors.